Hubungan Antara Pajanan Pestisida dengan Kejadian Dislipidemi pada Wanita Usia Subur (WUS) di Desa Gombong Kecamatan Belik Kabupaten Pemalang - Budiono, Slamet; Suhartono, Suhartono; Nurjazuli, Nurjazuli (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2013)
Background: One of the impact of pesticide exposure to women of childbearing age is dislipidemia. Dislipidemiaon women can cause reproductive disorder such as infertility, spontaneous abostion, fetal growth disordere andpremature birth. This research aimed is to prove that pesticide exposure is the risk factor for dislipidemi on WCA.Method: It was a cross-sectional study on 38 subjects Pesticide exposure was measured by asking WCAâ€™s involvementin agricultural activities using structured questionnaire and by checking their level of cholinesterase. Incidenceof dislipidemi measured using blood lipid profile parameters (total cholesterol, HDL, LDL and triglycerides).Confounding variables included in this research were age, level of education, nutritional status, hormonalparticipation KB, cigarette smoke exposure history.Result: The prevalence of dislipidemi on WCA was 44.7%. Subjects with cholinesterase levels below the averagewere 20 people (52.6%) with a mean Â± SD was 8.9395+1.37556. Pesticide exposure is a risk factor dislipidemi (p= 0.024, 95% CI = 1.167 to 6.094).Conclusion: The higher the degree of exposure to pesticides, the greater the risk of dislipidemia. Based on dataand theory study, the pathogenesis of dislipidemi allegedly through the barriers of lipase function, thyroid hormoneresistance and the accumulation of pollutants in fatty tissue.Keywords: Exposure to Pesticides, lipid profile, dislipidemi.